Advances in health care management. Vol. 1 - Fottler, Myron D.; Savage, Grant T. 1954-; Blair, John D. 1944- (Advances in health care management., 2000)
Advances in Health Care Management is a research annual that publishes state-of-the-art reviews and research on special topics in the field of health care management. As conceived by the founding editors, John D. Blair, Myron D. Fottler, and Grant T. Savage, and as originally commissioned by JAI Press, Advances in Health Care Management provides a forum for leading research on health care management. Volumes 1-3 offer reviews of the field, research on selected topics, and best papers from the Health Care Management Division of the Academy of Management.